2008
DOI: 10.1007/s00128-008-9530-6
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Toxic Metals in Multisectoral Samples from Winam Gulf of Lake Victoria

Abstract: In this study, the distribution and sources of inputs of trace metals including Cd, Cu, Zn and Pb from various sources as well as Fe which is widely used in the construction industry, into Winam Gulf of Lake Victoria were investigated. The sampling sites were located up streams and down streams of four rivers (Sio, Nyamasaria, Nyando and Sondu-Miriu), in four beaches along the lake (Port Victoria, Kisumu Car Wash, Dunga and Hippo point beaches) and in three estates (Nyamasaria, Migosi and Nyawita) in Kisumu ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…Recent research has shown that Lake Victoria is contaminated with pesticide residues, metals and polycyclic aromatic hydrocarbons (PAHs), especially the Winam Gulf part, where concentrations sometimes exceed the guideline limits for drinking water and aquatic life (Kwach and Lalah, 2009;Ongeri et al, 2009;Wasswa et al, 2011;Onyango et al, 2012). Some contaminants have also been detected in edible parts of the three most common fish species Nile perch (Lates niloticus), tilapia (Oreochromis niloticus) and Darga (Rastrineobola argentea).…”
Section: Introductionmentioning
confidence: 97%
“…Recent research has shown that Lake Victoria is contaminated with pesticide residues, metals and polycyclic aromatic hydrocarbons (PAHs), especially the Winam Gulf part, where concentrations sometimes exceed the guideline limits for drinking water and aquatic life (Kwach and Lalah, 2009;Ongeri et al, 2009;Wasswa et al, 2011;Onyango et al, 2012). Some contaminants have also been detected in edible parts of the three most common fish species Nile perch (Lates niloticus), tilapia (Oreochromis niloticus) and Darga (Rastrineobola argentea).…”
Section: Introductionmentioning
confidence: 97%
“…The observed concentration ranges of individual toxic metals in the bottom sediments of water bodies in the Upper Silesia region (181.7-35200.0 ppm for zinc, 33.3-1648.8 ppm for lead, 1.8-359 ppm for cadmium, 14.0-271.5 ppm for copper, 45.3-167.5 ppm for chromium, and 12.0-128.5 ppm for nickel) should be considered spectacular or, at a minimum, rarely found, taking into account the results of comparable studies conducted in other parts of the world (Dauvalter, 1994;Khan et al, 1995;Szymanowska et al, 1999;Lindström and Håkanson, 2001;Magiera et al, 2002;An and Kampbell, 2003;Ikem et al, 2003;Kosov et al, 2004;Wang et al, 2004;Nguyen et al, 2005;Roach, 2005;Duman et al, 2007;Gantidis et al, 2007;Ochieng et al, 2007;Ongeri et al, 2009;Baek and An, 2010;Mutia et al, 2012;Hahladakis et al, 2013;Jagus et al, 2013).…”
Section: Comparison With Literature Datamentioning
confidence: 95%
“…There are also many industrial activities, such as textile manufacturing, food processing, and pulp and paper production, that are recognized as sources of untreated wastewater flowing into rivers and the lake (Nyenje et al, ; Verschuren et al, ). Heavy metal pollution in river and lake waters has also been observed, as a result of alluvial gold‐mining in the basin (Ongeri, Lalah, Wandiga, Schramm, & Michalke, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are also many industrial activities, such as textile manufacturing, food processing, and pulp and paper production, that are recognized as sources of untreated wastewater flowing into rivers and the lake (Nyenje et al, 2010;Verschuren et al, 2002). Heavy metal pollution in river and lake waters has also been observed, as a result of alluvial gold-mining in the basin (Ongeri, Lalah, Wandiga, Schramm, & Michalke, 2009). Although many studies have focused on the recent impacts of these developments on freshwater biodiversity (Jackson, Woodford, & Weyl, 2016;Lange, Kristensen, & Madsen, 2013), very few have attempted to project the impacts of future land-use changes.…”
Section: Introductionmentioning
confidence: 99%